Islamic Educational Values in the Baantaran Jujuran Tradition in Banjar Community Weddings - Latifah Latifah; Nuril Huda (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Indonesia, as a multicultural country, has a variety of traditions in the implementation of customary weddings. One of these is the baantaran jujuran tradition practiced by the Banjar community. Baantaran jujuran is a ceremony in which the groom’s family formally hands over the jujuran money to the bride’s family, a process that is rich with Islamic educational values. Therefore, the objective of this study is to analyze the Islamic educational values contained within the baantaran jujuran tradition. This research employs field research with a descriptive qualitative approach and is located in Sungai Gampa Village, Rantau Badauh District. The data collection techniques used include observation, interviews, and documentation. The findings are as follows: (1) Baantaran jujuran is a ceremony for the formal handover of jujuran money, the amount of which has been mutually agreed upon by both parties. Jujuran refers to a sum of wealth given by the groom’s family to the bride’s family as part of the marriage process. During this ceremony, various offerings or gifts are also presented; (2) The Islamic educational values contained in the baantaran jujuran tradition include values of tawhid, worship, morality, and social education. The value of tawhid education is reflected in the recitation of the two declarations of faith (syahadat). The value of worship education is reflected in the recitation of prayers and shalawat. The moral education value can be seen in the giving of offerings (gifts), which represents the responsibility of a husband. Lastly, the social education value is reflected in the mutual deliberation and strengthening of ties between both families as well as with surrounding neighbors. This study is important because it highlights the internalization between Islamic educational values and local traditions, while also serving as an effort to preserve national culture so that it does not fade with the progress of time